Media clips on social fear to regulate individual behavior in temporary involuntary isolation (quarantine) - Olkhovaya, Tatyana A.; Sorokoumova, Elena A.; Mashkin, Nikolai A.; Vinogradova, Tatyana S.; Aytuganova, Jhanna I.; Romanov, Igor V.; Gots, Evgeniya V.; Pozdnyakova, Irina R. (Cuestiones Políticas, 2020)
The objective of the research was to study the manifestation of the emotion of fear in the context of the COVID-19 pandemic and to determine the details of its application in the clips of social networks. As a research method, the authors used the questionnaire survey to collect primary information. The novelty and originality of the study lies in the fact that the phenomenon of social fear in temporary forced isolation is investigated. For the first time, it is discovered that the overall goal of social media videos affecting the emotion of fear is to create a common problem that forces potential viewers to choose self-isolation. It is concluded that the analysis of the clips from social networks revealed four main directions to position the emotion of fear: fear associated with a direct threat to the life activity of individuals; fear caused by unforeseen situations; fear associated with situations that can be harmful to health; fear associated with non-conformity with certain values and norms accepted in society, with the fear of differing from established standards and benchmarks.